Prinsip Good Governance Guna Pengelolaan Akuntansi Publik dan Pengawasan pada Kelompok Masyarakat di Kelurahan Bendogerit Kota Blitar - Ulva Roifatul Lailin; Putri Cinta Mei; Riska Dwi Puswandari (Transgenera: Jurnal Sosial, Politik dan Humaniora, 2025)
This research aims to analyze the application of good governance principles in public accounting management and supervision of community groups in Bendogerit Village, Blitar City. Good governance, which includes the principles of transparency, accountability, participation, effectiveness and efficiency, is the main framework for improving the quality of public financial governance at the community level. The aim of this research is to evaluate how the principles of good governance are applied in the management of public accounting and supervision of community groups in Bendogerit Village, Blitar City. The research method used is a qualitative approach with data collection techniques in the form of in-depth interviews, direct observation and document analysis. Research participants included community group administrators, community leaders, and sub-district government officials. The author conducted this research to see how transparency, accountability, participation and responsiveness are implemented in public accounting management practices at the sub-district level. They also look at how oversight systems are implemented to ensure that public funds are used effectively and according to purpose. This research uses a qualitative approach that uses observation, documentation and interviews to collect data. The research results show that the implementation of good governance principles in Bendogerit Village still faces challenges, especially in terms of information disclosure and community involvement in the financial management process. However, there have been significant efforts by community groups and sub-district governments to increase transparency and accountability through better financial reporting and monitoring mechanisms that involve the community. Research shows that, even though the principles of good governance have been implemented, transparency of financial information and community involvement in the supervisory process are still problems. It is recommended that stakeholders in Bendogerit Subdistrict strengthen the monitoring system based on community participation and increase awareness of the importance of good public accounting management. The conclusion of this research emphasizes the importance of training and assistance in managing public accounting, applying information technology to support transparency, and strengthening collaboration between community groups and the government. The recommendations provided include strengthening local regulations, optimizing community participation, and developing a more inclusive supervisory system to support good financial governance.